Pat Andares - Headache - Ralitsa Akins (MedEdPORTAL, 2011)
Abstract Introduction This case was created for use with standardized patients (SPs) for teaching and/or evaluation purposes, in hopes of enriching the library of case scenarios available to SP trainers and medical school faculty for objective structured clinical examinations (OSCEs). The case is intended for teaching/examination of medical students years 1 through 4 (depending on a medical school's type of curriculum), as well as for resident and faculty development. Methods The case requires 15 minutes for the learner in the patient room, 10 minutes for the patient note, and 30 minutes for debriefing with a faculty-observer (for teaching purposes only). Mr./Ms. Pat Andares is a 59-year-old patient presenting with a severe headache that started yesterday after a stressful day at work. The patient went to sleep hoping that the headache was a sign of being tired; s/he was not able to sleep well during the night, and this morning the headache was still very bad. In addition, the patient fell down this morning when trying to get out of bed. On physical examination, the patient is agitated and has trouble choosing words, with speech somewhat effortful. Results Interrater reliability was assessed on a continuous basis at the originating program, and for 20 consecutive cases was above 80%. Additionally, a case study was completed to review the interrater reliability between SPs and faculty-observers in a multiple-station high-stakes OSCE examination. Results indicated faculty and SPs matched in scoring. Discussion This case has been successfully implemented with students at the Texas Tech University Health Sciences Center Paul L. Foster School of Medicine.